Monitoring and Evaluation of Emotion Regulation by Aerobic Exercise and Motor Imagery Based on Functional Near-Infrared Spectroscopy - Ding, Peng; Wang, Fawang; Li, Siyu; Zhang, Wei; Li, Hongquan; Chen, Zhuangfei; Zhao, Lei; Gong, Anmin; Fu, Yunfa (Frontiers in Computational Neuroscience, 2021)
Objective. Functional near-infrared spectroscopy (fNIRS) is used to monitor and evaluate emotion regulation by aerobic exercise and motor imagery in the study. Approach. 30 subjects were scored by State-Trait Anxiety Inventory (STAI) and Profile of Mood States (POMS) and fNIRS were collected before, after and during aerobic exercise and motor imagery, and then oxygenated hemoglobin (HbO), deoxygenated hemoglobin (HbR) and total hemoglobin (HbT) concentration and their average value were calculated, and the ratio of HbO concentration in left and right frontal lobe were also calculated; Spearman correlation coefficient was used to calculate the correlation between variation in the average score of two scales and variation in blood oxygen concentration. Main results. After regulating emotion by aerobic exercise, the scores of the STAI and POMS of 15 subjects had significant changes and the average scores of the two scales decreased by 7.27 and 27, respectively. Statistical analysis of fNIRS showed that the average HbO and HbT concentrations before and after changes. The ratio of the HbO concentration changes of left and right frontal lobe before and after aerobic exercise was lateralized with right hemisphere dominance, and the ratio of regulating emotion by aerobic exercise have significant the HbO concentration changes before and after aerobic exercise was higher than that of motor imagery. Spearman correlation coefficient calculation showed that the score changes of the STAI and POMS before and after regulating emotion by aerobic exercise were completely negatively correlated with HbO, HbR and HbT concentration changes. Motor imagery has no significant effect on emotion regulation. Significance. The study showed that a portable fNIRS could be effectively used for monitoring and evaluation of emotion regulation by aerobic exercise. The study is expected to provide ideas for constructing fNIRS based online real-time monitoring and evaluation of emotion regulation by aerobic exercise.